Post Dengue Infectious Syndrome - Azmi, Maliha; Nasim, Asma; Dodani, Sunil (Infectious Diseases Journal of Pakistan, 2023)
We are sharing here a rare condition in a patient who had persistent debilitating systemic symptoms after resolution of acute dengue fever. A 35y/o male patient was diagnosed with post dengue infectious syndrome after other autoimmune etiologies were ruled out. Our patient was treated symptomatically and improved after four months.